Pengelolaan Lingkungan dan Kondisi Masyarakat Pada Wilayah Hilir Sungai - Suganda, Emirhadi; Yatmo, Yandi Andri; Atmodiwirjo, Paramita (Makara Human Behavior Studies in Asia, 2009)
River by nature is a unity, but there is a tendency to separate river management based on administrative areas. River is also related to the community living in its surrounding area. This paper discusses watershed issues related to the management and community condition, especially within the framework of interrelationship between upstream and downstream areas. Department of Public Works as the institution was responsible for the national water resource management has proposed the idea of "one river one plan one management." However, in reality this idea is not consistent with the regulations issued by the government, especially in the context of regional autonomy. This paper also attempts to illustrate the condition of settlement and community condition in Bale Kambang and Kampung Pulo as downstream areas. The findings of this study suggest the needs for an integrated management for various watershed areas, with the understanding of community condition in those areas. The findings provide inputs for planning and managing of urban areas by putting an emphasis on the interrelationship between various areas of wathershed, as well as the physical environment of watershed and the community condition of the surrounding communities.